Virus and Viroid-Derived Small RNAs as Modulators of Host Gene Expression: Molecular Insights Into Pathogenesis - Ramesh, S. V.; Yogindran, Sneha; Gnanasekaran, Prabu; Chakraborty, Supriya; Winter, Stephan; Pappu, Hanu R. (Frontiers in Microbiology, 2021)
Virus-derived siRNAs (vsiRNAs) generated by the host RNA silencing mechanism are effectors of plant’s defense response and act by targeting the viral RNAand DNA in post-transcriptional gene silencing (PTGS) and transcriptional gene silencing (TGS) pathways, respectively. Contrarily, viral suppressors of RNA silencing (VSRs) compromise the host RNA silencing pathwaysand also causedisease-associated symptoms. In this backdrop, reports describing the modulation of plant gene(s) expression byvsiRNAsvia sequence complementarity between viral small RNAs (sRNAs) and host mRNAs, have emerged.In some cases, silencing of host mRNAsbyvsiRNAshas been implicated to cause characteristic symptoms of the viral diseases. Similarly, viroid infection results in generation of sRNAs, originating from viroid genomic RNAs, that potentially target host mRNAs causing typical disease-associated symptoms. Pathogen-derived sRNAs have been shown to have the propensity to target wide range of genes including host defense-related genes, genes involved in flowering and reproductive pathways.Recent evidence indicates that vsiRNAs inhibit host RNA silencing to promote viral infection by acting as decoy sRNAs. Nevertheless, it remains unclear if the silencing of host transcripts by viral genome-derived sRNAsare inadvertent effects due to fortuitous pairing between vsiRNA and host mRNA or the result of genuine counter-defense strategy employed by viruses to enhance its survival inside the plant cell. In this review we analyze the instances of such cross reaction between pathogen-derived vsiRNAs and host mRNAs and discuss the molecular insights regarding the process of pathogenesis.